Does preoperative depression predict post-operative surgical pain: A systematic review. (May 2017) - Dadgostar, Anali; Bigder, Mark; Punjani, Nahid; Lozo, Svjetlana; Chahal, Vickramjit; Kavanagh, Alexander
Abstract: Background: As surgical procedures have been developed and refined, determining which factors predict rapid and successful surgical outcomes has become a priority. Significant psychosocial influences on surgical outcomes have been found with numerous procedures. The objective of this study is to perform a systematic review of randomized-control trials and observational studies to examine the relationships between pre-operative depression and post-operative (<6 weeks) pain outcomes. Materials and methods: Pubmed/MEDLINE, EMBASE, CINAHL and Web of Science were searched for studies published from January 1, 2006 and August 31, 2016. Two independent reviewers assessed the eligibility of each report based on predefined inclusion criteria (study design, measure of pre-operative depression, and post-operative pain). Participants included adult patients undergoing surgical procedures diagnosed with depression pre-operatively. Patients were assessed for post-operative pain via pain scales and use of post-operative pain medications. Data was summarized qualitatively due to limitations of comparability and transformation. Significant clinical and statistical heterogeneity of the included studies was identified. Results: Of 1091 abstracts reviewed, 18 studies met the inclusion criteria. Due to the significant clinical and statistical heterogeneity, a meta-analysis was not performed. 8 studies (comprising a total of 1314 patients) reported a statistically significant effect of pre-operative depression on post-operative pain. 10 studies encompassing a total 1226 patients failed to demonstrate a statistically significant effect of depression on postoperative pain. Conclusion: The analysis of results was limited to a systematic review and qualitative analysis of the eligible studies. Based on this systematic review we identified 8 studies reporting a statistically significant effect of pre-operative depression on post-operative pain and 10 studies reporting no statistically significant effect of pre-operative depression on post-operative pain. Therefore, the quality of presented data is poor and makes it challenging to answer further questions. Large epidemiologic studies in this field are needed to provide further evidence. Highlights: Systematic review of pre-operative depression and post-operative pain was performed. 8 studies reported a statistically significant effect. 10 studies did not demonstrate a statistically significant effect. There is a vast degree of heterogeneity inherently within these studies. There is a lack of randomized controlled trials in this field.